Role Stressor, Work Stress and Cyberloafing Behavior: Will They Decrease The Employee Performace? - Sih Darmi Astuti; Tito Aditya Perdana; Rauly Sijabat (LPPM Universitas Terbuka, 2024)
Purpose – The empirical studies regarding the effect of cyberloafing behavior on employee performance have been widely studied. However, the results of the studies still show inconclusive results. Based on this research gap, this study was conducted to re-examine the influence of role stressors and work stress in explaining cyberloafing behavior that impacts employee performance. Methodology – The test was carried out to examine the empirical model and research hypothesis using the Structural Equation Modeling approach. Employees who work in various industries whose companies are located in the city of Semarang are the respondents of this research collected using a questionnaire consisting of statements developed from variable measurement indicators using closed answers with alternative answers provided on a scale of 1-10. Findings – The test results show that the role stressor has a significant positive effect on work stress. The test results also show that role stressors has proven to have a significant positive effect on cyberloafing behavior, while work stress cannot prove its effect. The research also proves that cyberloafing behavior has a real effect in explaining employee performance. Originality – This research studies the empirical effect of cyberloafing behavior which has not been done by previous research.